2022
DOI: 10.3233/bpl-210136
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B and Muscular Strength are Independently Associated with Cognitive Control

Abstract: Although muscular strength has been linked to greater cognitive function across different cognitive domains, the mechanism(s) through which this occurs remain(s) poorly understood. Indeed, while an emerging body of literature suggests peripheral myokines released from muscular contractions may play a role in this relationship, additional research is needed to understand this link. Accordingly, this study sought to compare the influences of a particular myokine, Cathepsin B (CTSB), and muscular strength on hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The benefits of exercise may be communicated to the brain via factors secreted from peripheral organs, comprehensively referred to as exerkines [113]. These include myokines [114,115] such as VEGF [116] irisin [117][118][119] and Cathepsin B [30,[120][121][122] as well as the myometabolite lactate [98]. In addition, hepatokines (insulin-like growth factor ( [123], clusterin [124], glycerophosphoryl diester phosphodiesterase-like protein [125]), adipokines [126], and blood platelets [127] derived from runners have been shown to play a role in neural plasticity or cognition [128][129][130].…”
Section: Peripheral Organ-brain Crosstalkmentioning
confidence: 99%
“…The benefits of exercise may be communicated to the brain via factors secreted from peripheral organs, comprehensively referred to as exerkines [113]. These include myokines [114,115] such as VEGF [116] irisin [117][118][119] and Cathepsin B [30,[120][121][122] as well as the myometabolite lactate [98]. In addition, hepatokines (insulin-like growth factor ( [123], clusterin [124], glycerophosphoryl diester phosphodiesterase-like protein [125]), adipokines [126], and blood platelets [127] derived from runners have been shown to play a role in neural plasticity or cognition [128][129][130].…”
Section: Peripheral Organ-brain Crosstalkmentioning
confidence: 99%
“…In this study it was found that the latency of event related potentials an electrophysiological correlate of a cognitive task, the Flanker task, was inversely correlated with performance on the task. Thus, this study reports the novel finding that CTSB may play a role in cognitive control by modulating processing speed [ 8 ]. The final research paper pertains to effects of moderate-intensity exercise and high-intensity interval exercise on serum BDNF levels and working memory in young adult females.…”
mentioning
confidence: 99%